Serena Garza COVID-19 Narrative, Part 2 - Garza, Serena::::::::: (2021)
In this three-part reflection, Garza empathizes with children who are unable to celebrate birthdays or play with school mates, and expresses employment concerns such as job loss, filing for unemployment, and wearing face masks in the workplace.